Three new species of Lepanthes (Orchidaceae) - Larsen, Bruno (Phytotaxa, 2014)
In this paper three new species of Lepanthes (Orchidaceae: Pleurothallidinae) from Ecuador, Panama and Venezuela are described. Each species is illustrated with a line drawing. For each of the new species information about distribution, habitat, and a comparison with similar taxa is given. The new species are named: Lepanthes dubbeldamii, Lepanthes liesiae and Lepanthes luerorum.